APPLICATION OF AUTOMATION HYDROPONIC PLANTING SYSTEM BASED ON ACIDITY, NUTRIENT CONCENTRATION AND LIGHTING - Sevy Diantika Putri; Abdullah Abdullah (FISITEK: Jurnal Ilmu Fisika dan Teknologi, 2021)
Research Hydroponic plants are an alternative solution for urban communities so that they can grow crops at home and do not require large areas of land. However, hydroponic farmers sometimes find it difficult to improve plant quality because they are busy and do not have time to take care of the condition of the plants. Therefore, an automatic system was designed to improve the quality of hydroponic plants. The test results show that this tool is able to control pH levels, namely when the pH is too acidic, the base pH pump will turn ON to normal, when the pH is too base, the acid pump will turn on to normal. To control nutrient solids, namely when nutrients are reduced, the nutrient pump will be ON and when there is excess the water pump will be ON to neutralize it as needed by the plant every week, controlling day and night conditions, namely during the day the system will work to drain the plants and at night the hydroponic irrigation will stop for efficiency tool, and all sensor values are displayed through the LCD which monitoring the activity of the tool. Therefore, from the system that has been designed, the tool is able to work automatically on the application of automation hydroponic planting system based on acidity, nutrient concentration and lighting.